Capsaicin‐Decorated Semiconducting Polymer Nanoparticles for Light‐Controlled Calcium‐Overload/Photodynamic Combination Therapy - Ni, Xiaoyue; Shi, Wenheng; Liu, Yaxin; Yin, Likun; Guo, Zixin; Zhou, Wen; Fan, Quli (Small (Weinheim an der Bergstrasse, Germany), 2022)
Calcium‐overload cancer therapy has gained more and more attention owing to its good therapeutic efficacy with low side effect. However, conventional calcium‐overload therapy is achieved by introducing an additional calcium element into the tumor site by nanomedicines, which may also lead to the calcium‐overload of normal organs, causing an undesirable side effect. To address such issues, capsaicin‐decorated semiconducting polymer nanoparticles (CSPN) are designed to modulate the calcium ion channel of cancer cells for calcium‐overload cancer therapy without adding an additional calcium element. CSPN is composed of a near‐infrared (NIR) absorbing semiconducting polymer (SP) PCPDTBT and a capsaicin‐conjugated amphiphilic copolymer, PEG‐PHEMA‐Cap. Under NIR laser irradiation, PCPDTBT can generate singlet oxygen (1O2), which not only triggers the release of capsaicin, but also induces photodynamic therapy (PDT). The released capsaicin can further activate transient receptor potential cation channel subfamily V member 1 (TRPV1) of U373 cancer cells, leading to an influx of calcium ions into cells. In addition, the intense NIR‐II fluorescence signal of CSPN makes it suitable for tumor imaging. Thus, this study develops a tumor specific nanotheranostic system for NIR‐II fluorescence imaging‐guided calcium‐overload/PDT combination therapy. Capsaicin‐decorated semiconducting polymer nanoparticles (CSPN) are designed for calcium‐overload/photodynamic combination therapy. Under laser irradiation, capsaicin will release from CSPN, which can activate transient receptor potential cation channel subfamily V member 1 (TRPV1) of U373 cancer cells, leading to calcium‐overload‐mediated cell death. Such a nanosystem can achieve efficient calcium‐overload therapy without introducing external calcium, showing minimized side effects towards normal organs.